The Family Management of Childhood Chronic Conditions: Measurement in a Turkish Sample - ERGÜN, AYŞE; ŞİŞMAN, FATMA NEVİN; KADIOĞLU, HASİBE; GÜR, KAMER; KOLAÇ, NURCAN; EROL, SAİME (ELSEVIER SCIENCE INC, 2019)
Purpose: The principal aim of this study was to adapt the FaMM into the Turkish language and test its validity and reliability. Design and methods: Data were collected from a total of 395 parents of children with chronic disease. The FaMM was translated using the translation and back-translation method. The reliability analysis of the FaMM was performed using Cronbach alpha coefficients, item-total correlations and test-retest correlations. Construct validity for the scale was assessed with confirmatory factor analysis (CFA) and exploratory factor analysis (EFA). Results: The overall content validity index was 95%, signifying that the FaMM has good content validity. The CFA of the Turkish version of the FaMM did not confirm the original factorial structure. The model of three subscales for the Turkish FaMM was validated using EFA. The values of >= 0.70 for the Cronbach alpha coefficient, >0.25 for the item-total correlations and >0.40 for the test-retest application correlations for 2 weeks were found to be acceptable levels for the instruments and its subscales. Conclusions: The FaMM was found to be valid, reliable and appropriate for Turkish culture and psychometric characteristics were satisfactory. Practice implications: The FaMM can be used in evaluating the management of illness in families with children with chronic disease. (C) 2019 Elsevier Inc. All rights reserved.
Keywords: Children's chronic conditions; Family illness management; Instrument adaptation; STYLE FRAMEWORK; CHILDREN; ADOLESCENTS; ADAPTATION; VALIDATION; PATTERNS; LIFE